Student modelling in an intelligent computer assisted language learning system the issues of language transfer and learning strategies - Bull, Susan; Pain, Helen; Brna, Paul (1993)
Abstract: "This paper presents the student model of an intelligent computer assisted language learning (ICALL) system to facilitate the acquisition of clitic pronoun placement in European Portuguese. The student model is the focal point of the system; it is inspectable, and can be modified through user/system negotiation (both to obtain a more accurate model and to promote learner reflection). The paper describes the evaluation of the initial learner profile which is used as the basis upon which to construct a more detailed student model during the interactions which follow. The information to be obtained relates to the learner's native and foreign language background, his use of language learning strategies, and his proficiency in Portuguese. The manner in which the learner's background languages and learning strategies relate to the student model is described, and user reactions to this approach are presented in order to demonstrate its validity."
Keywords: Bionics and artificial intelligence; Education and training; Linguistics; Linguistik; Computer-assisted instruction